Membangun Ketahanan Keluarga Di Masa Pandemi: Studi Fenomenologi Terhadap Bisnis Dropship Di Kota Langsa - Dessy Asnita; Agustinar (Hukum Keluarga Islam IAIN LANGSA, 2022)
Dropshipping has an important role in family resilience, because one of the factors that support and hinder family resilience is economic problems. Dropshipping business is a solution and alternative that is quite attractive because it is easy to do with only a gadget and internet quota and does not spend a large amount of capital, is flexible (not bound by time). This dropship system business can help the family economy. During this pandemic, people must be more productive and innovative. This study aims to find out how to build family resilience through a dropshipping business during the covid-19 pandemic. This research was conducted with a qualitative approach with descriptive analysis and using a data collection system with observations, interviews and documentation. The methodology used is an enomenological study. Based on the results of the study, it can be concluded that the way to build a dropshipping system for family resilience is to make products as attractive as possible and utilize digital media in the era of the Covid-19 pandemic.